The mechanism – between applicability and artistic concept – on the axis of antiquity, Middle Ages and modernism - Răzvan-Petrișor Dragoș (Anastasis: Research in Medieval Culture and Art)
In Antiquity, civilization meant the invasive intervention on nature and the environment through deforestation, landscape changes, the extinction on fauna and flora and so on. Both in Antiquity and in the Middle Ages, technology was closely related to the production of material goods, construction, agriculture and trade, without being associated with the idea of art, so we cannot talk about any aesthetics of mechanisms. We can say that the devices made for the plays or “automata” type mechanisms from the time between the end of Antiquity and the Middle Ages, were a preamble to visual arts of technological origin. Starting with the Renaissance, “automata” devices migrated to a new environment: that of small circles, formed by the high society. After less than three millennia of scientific evolution, today one can speak about artificial consciousness and the transcendence of the physical capacities of beings. The robot, in the philosophical sense, is an interpretation of the living body that exercises its capabilities in its own repetitive manner. The illustration of mechanisms by engineers has been common since the Renaissance. Of all the inventors of the Renaissance and of all times, one stands out in particular, namely Leonardo Da Vinci. From the issue of pagination, spatiality and shapes circumscribed in geometric structures, Leonardo pleaded for both technical and visual solutions. One conclusion of the above is that through technical valences they could borrow from art, mechanisms have caught people's attention since time immemorial, so we will find countless applications of them throughout history.